Alternative Approach for the Calculation of Magnetic Field due to Magnet for Magnetic Field Visualization and Evaluation - Kaphle, Kishor; Karki, Gyanendra; Panthi, Amrit (Journal of the Institute of Engineering, 2020)
The magnetic field of different geometry of the permanent magnet is analytically calculated by using basic principles of the magnetism in very easier approach. Concept of origin shifting and geometrical shape transformation are used to formulate the formula for cuboidal, cubical and cylindrical permanent magnets. This concept can be used for the analysis of magnetic field distribution in space around for permanent magnet as well as electromagnet in a very easier approach. Handy and simplified software is made to calculate the magnetic field due to permanent magnet and electromagnet at any desired position on space. Magnetic field visualization is also done in both magnitude and direction by using MATLAB.